Long-range coupling in cyclic silanes. Issue 42 (20th October 2020) - Ferguson, John T.; Jiang, Qifeng; Marro, Eric A.; Siegler, Maxime A.; Klausen, Rebekka S.
Abstract : We report the synthesis of a mixed methyl- and hydro-substituted cyclosilane (1 ) possessing cis / trans stereoisomerism. Abstract : We report the synthesis of a mixed methyl- and hydro-substituted cyclosilane (1 ) possessing cis / trans stereoisomerism. Each diastereomer of 1 possesses distinct symmetry elements ( cis -1 : C s -symmetric; trans -1 : C 2 -symmetric). Cyclosilane 1 is a model system to probe configuration- and conformation-dependent long-range proton–proton coupling. Extensive NMR spectroscopic characterization is reported, including one-dimensional 1 H NMR and 29 Si DEPT and INEPT+ spectra and two-dimensional 1 H– 29 Si and 1 H– 1 H correlated spectroscopy (HSQC, HMBC, COSY). On the basis of these experiments, molecular connectivity consistent with four-bond 1 H– 1 H coupling is confirmed.